Research focus and emerging trends of the gut microbiome and infant: a bibliometric analysis from 2004 to 2024 - Yang, Ru; Shi, Zeyao; Li, Yuan; Huang, Xi; Li, Yingxin; Li, Xia; Chen, Qiong; Hu, Yanling; Li, Xiaowen (Frontiers in Microbiology, 2024)
BackgroundOver the past two decades, gut microbiota has demonstrated unprecedented potential in human diseases and health. The gut microbiota in early life is crucial for later health outcomes. This study aims to reveal the knowledge collaboration network, research hotspots, and explore the emerging trends in the fields of infant and gut microbiome using bibliometric analysis.MethodWe searched the literature on infant and gut microbiome in the Web of Science Core Collection (WOSCC) database from 2004 to 2024. CiteSpace V (version: 6.3.R1) and VOSview (version: 1.6.20) were used to display the top authors, journals, institutions, countries, authors, keywords, co-cited articles, and potential trends.ResultsA total of 9,899 documents were retrieved from the Web of Science Core Collection. The United States, China, and Italy were the three most productive countries with 3,163, 1,510, and 660 publications. The University of California System was the most prolific institution (524 publications). Van Sinderen, Douwe from University College Cork of Ireland was the most impactful author. Many studies have focused on atopic dermatitis (AD), necrotizing enterocolitis (NEC), as well as the immune mechanisms and microbial treatments for these diseases, such as probiotic strains mixtures and human milk oligosaccharides (HMOs). The mother-to-infant microbiome transmission, chain fatty acids, and butyrate maybe the emerging trends.ConclusionThis study provided an overview of the knowledge structure of infant and gut microbiome, as well as a reference for future research.